###### Asked in Algebra

Algebra

# What are the 3 solutions of the equation y 2x?

**We need you to answer this question!**

###### If you know the answer to this question, please register to join our limited beta program and start the conversation right now!

## Related Questions

###### Asked in Algebra, Math and Arithmetic, Calculus

### How do you solve y equals x plus 3 and -2x plus y equals -4?

(1) y = x + 3
(2)-2x + y = -4
It is usual to present the equations showing one unknown
expressed in terms of the other unknown. This is already the case
in Equation (1).
Restructuring Equation (2) gives y = 2x -4
(1) y = x + 3
(3) y = 2x - 4 Now subtract Equation (1) from Equation (3) to
eliminate y.
y - y = 2x - x -4 -3 : 0 = x - 7 : x = 7
Substitute for x in Equation (1)
y = 7 + 3 : y = 10

###### Asked in Math and Arithmetic, Algebra, Geometry

### What are the solutions to the simultaneous equation of 2x plus y equals 5 and x squared -y squared equals 3 showing work?

2x + y = 5 . . . thus y = 5 - 2x
x2 - y2= 3 . . . . now substitute for y in this equation.
x2 - (5 - 2x)2 = 3 . . . and after expansion this becomes,
x2 - 25 + 20x - 4x2 = 3
-3x2 + 20x - 28 = 0 . . . and this factors as,
(-3x + 14)(x - 2) = 0
Then, x = 2 , x = 14/3
When x = 2, then 2x + y = 5 gives the result y = 1.
When x = 14/3 then 2x + y = 5 gives the result y = -13/3.

###### Asked in Algebra, Calculus

### What is the answer for this equation 2x-y equals 3and x plus y equals 6?

A system of equations?
2X - Y = 3
X + Y = 6
I will try substitution. Express one variable in terms of the
other ( use X + Y = 6 )
X + Y = 6
Y = - X + 6
insert into other equation
2X - ( - X + 6) = 3
2X + X - 6 = 3
3X = 9
X = 3
-------
put that back into one of the equations
(3) + Y = 6
Y = 3
-------
check both equations
2(3) - (3) = 3
6 - 3 = 3
3 = 3
first equation checks
(3) + (3) = 6
6 = 6
Both equations check
X = 3
Y = 3
are both true solutions for this system of equations

Load More